Alternative Regimes of Transnational Environmental Certification: Governance, Marketization, and Place in Alaska's Salmon Fisheries. (November 2013) - Foley, Paul; Hébert, Karen
Transnational certification and ecolabeling programs have become an important new site of environmental governance, as well as an emerging arena for action and conflict in international trade. This paper explores the implementation of Marine Stewardship Council (MSC) certification in salmon fisheries in the US state of Alaska in the early 2000s, the growing opposition within the industry to MSC certification through periods of reassessment, and the emergence of an alternative Alaska certification initiative in 2011. It suggests that these shifts were rooted in struggles over understudied third-party certification and labeling processes that we conceptualize as marketized governance. The paper further shows how certification and labeling can obscure and expose competing industry interests and power relations, provoke struggles over fisheries' social representation, and open up novel avenues for cooperation and change, indicating ambiguity in the social and cultural implications of neoliberal modes of governance. Finally, the paper suggests that the ascendancy of the MSC has sparked the emergence of new political and economic geographies of certification and ecolabeling in Alaska and other jurisdictions where place-specific and other initiatives vie for governance and market legitimacy.